Best Practices for the Ocean Moored Observatories - Venkatesan, Ramasamy; Ramesh, Krishnamoorthy; Kishor, Anand; Vedachalam, Narayanaswamy; Atmanand, Malayath A. (Frontiers in Marine Science, 2018)
Real-time spatio-temporal meteorological and oceanographic data from the Ocean moored observatories are essential for precise forecast of ocean state, climate variability studies and reliable weather prediction. Precise spatio-temporal measurement of subsurface parameters such as temperature, salinity and current are essential for understanding the intra-seasonal and inter-annual evolution of the monsoons and tropical cyclones. To cater to this time-critical information, moored observatories have to be continuously operational in the harsh marine environment by measuring these Essential Ocean Variables, though bio-fouling and corrosion limits the life time and accuracy of the highly precise measuring instruments. Thus, best practices in the moored observations are essential for accurate and cost-effective long term ocean observation. The Indian moored buoy network which is operational since 1997, has been providing quality data over the past one decade. This paper describes the best operational practices and quality control processes followed in the Indian moored buoy system design, sensor calibration, testing, integration, deployment, retrieval and data quality control over the past two decades, which has helped to achieving an average meteorological data return of 90 % .